Estimation of parameters of the pulmonary circulation from cardiac oscillations of the intrabronchial air. - González Beltrán, C.; Zarzosa Pérez, C. A. (Revista Mexicana de Ingenieria Biomedica, 1991)
The heart is a muscular organ whose anatomical and physiological properties allow it to behave like a double pump. By rhythmic contractions it drives the blood flow to the two circulatory systems: the pulmonary and the systemic. In vertebrates of exclusively pulmonary respiration, the heart is located inside the thoracic cavity, behind the sternum and between the lungs.